Chemical composition, characterization, and antimicrobial properties of Thymbra spicata essential oil-based nanoemulsions and its application on curd cheese - Kayiran, Serpil Demirci; Bolgen, Umay Merve Guven; Akgül, Ebru; Kadiroglu, Pinar; Cengiz, Nurten; Cevikelli, Tilbe; Onan, Deniz; Ozkan, Esra Eroglu; Bozdogan, Gizem; Boga, Mehmet; Ozogul, Yesim; Esatbeyoglu, Tuba; et al. (Frontiers in Nutrition, 2025)
Background and aimsThymbra spicata L. has been widely recognized as a food additive due to its therapeutic benefits and low toxicity risk. This study focuses on the chemical constituents of T. spicata essential oil, antimicrobial, and antioxidant properties of essential oil (EO)-based nanoemulsions (NEs) and for the first time their effect on the preservation of curd cheese.MethodsNanoemulsions containing three different concentrations of EO (1%, 3%, and 5%) were tested for conductivity, droplet size, pH, polydispersity index (PDI), rheological properties, viscosity, and zeta potential. In addition, chemical composition was analyzed using gas chromatography-mass spectrometry. Moreover, the antimicrobial properties of the EOs and its nanoemulsion forms were evaluated in vitro against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Bacillus subtilis using the agar well diffusion assay. After in vitro studies, the nanoemulsion concentrations of 1%, 3%, and 5% and pure EO were incorporated into curd cheese. Curd cheese treatments were assessed in terms of total yeast and mold, mesophilic aerobic and lactic acid bacteria count, and quality analyses for 28 days.ResultsThe results showed that the dispersions with a spherical shape and droplet sizes were smaller than 165 nm for all three concentrations (154.9, 165.0, and 151.3 nm, respectively). All formulations maintained their physical properties even after stability tests. Major components in the essential oil (EO) were identified as γ-terpinene, thymol, carvacrol, and p-cymene. The nanoemulsion delayed the growth of mold and yeast for up to 28 days.ConclusionsConsequently, these findings indicate that T. spicata EO and derived nanoemulsions could be used as vital sources for developing new and impactful antimicrobial agents for food and different industries.